Gas Leakage and Fire Detector Based on Internet of Thing (IoT) Network (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The Internet of Things (IoT) is a growing network of interconnected devices equipped with various sensors and internet connectivity. This widespread adoption of IoT devices, particularly in industrial automation, has paved the way for real-time remote monitoring and control of industrial equipment. Traditional gas leak detection systems, while precise, fall short in effectively alerting people about leaks. To address this, we've developed an IoT-based gas leak detector with smart alerting capabilities. Our device utilizes data analytics on sensor readings to predict hazardous situations and send timely alerts to both concerned authorities and individuals in the vicinity, enabling proactive measures to mitigate potential risks. Thus, this gives manufacturers the ability to automate, and therefore optimize their operating efficiency. The purpose of this project is to introduce an industrial monitoring system design based on IoT networks. The proposed system is divided into two parts: the first part is to detect and identify the gas leakage level and fire alarm detector by using MQ-2 sensor. The second part is to monitor the proposed system based on thing speak. The thing speak is a cloud platform and it is an open-source of IoT application which can receive the sensors data via ESP32 module and plots these data in a field graph within various parameters.